Review of Regulatory Framework Governing Digital Tourism Information Center Program Based on Regulatory Impact Assessment (Law Research Review Quarterly, 2025)
This study evaluates the Tourism Information Center (TIC) Digital Nusantara’s regulatory framework regarding industrial efficiency. The primary issue is the fragmented, non-binding nature of current circular letters, leading to inconsistent implementation and budgetary waste. Using normative legal research and the Regulation Impact Assessment (RIA) framework, findings show that existing executive rule-making provides flexibility but fails to ensure national data integration. Aligned with Presidential Instruction No. 1/2025 on budget efficiency, this study concludes that a non-regulatory approach—revising technical guidelines and strengthening private-sector partnerships is more effective than creating rigid new regulations. Therefore, the government must prioritize data interoperability standards and formalize digital platform cooperation to ensure a cost-effective, integrated tourism ecosystem.